Skin sparing mastectomy and immediate reconstruction for breast cancer: a three to five year follow-up study of post-operative patients looking at cosmetic outcome - Muller, Elsie Maria (Department of Surgery, 2024)
Over 100 years ago Halsted described the radical mastectomy for early breast cancer. 1 This involved wide, en bloc removal of the tumour, normal surrounding structures of the chest wall, and contents of the axilla. For 75 years this remained the treatment of choice for women with breast cancer. Most tumours could be resected using this approach and local recurrences were rare. However, this radical surgical approach was associated with significant short- and long term morbidity. Removal of the pectoralis muscles resulted in major aesthetic chest wall deformity. Other complications involved impaired range of movement, chronic lymphoedema and poor quality of life. However, the most important weakness of radical mastectomy was its failure to influence long-term survival.